Ekonomi Islam (Sebuah Tinjauan Filsafat: Ontologi; Epistemologi; Aksiologi) - nahlah, nahlah; Arifin, Asriadi; Markarma, Muh. Ridwan (EKALAYA : Jurnal Ekonomi Akuntansi, 2024)
The purpose of this research is to concretely describe Islamic economic philosophy in terms of three aspects, namely Islamic economic epistemology, Islamic economic ontology and Islamic economic axiology. It is believed that the urgency of the contents of this article can add references for the perfection of Islamic economic research that will continue to be carried out in the future, so it is hoped that this article can become an additional reference in this research. This literature research takes written content from research that has been carried out previously and then elaborates it with current thinking until conclusions are drawn that show the substance of the current written content. The conclusion shows that the essence of science is based on aspects of objectives (ontology), methods of searching for truth (epistemology) and scientific values ​​(axiology), all of which are inherent in Islamic economic philosophy and it is a certainty that the main reference is sourced from the Qur'an and Hadith is a fundamental teaching that contains normative and positive values ​​in finding solutions to the economic problems faced.